Dose, Content, and Mediators of Family-Based Treatment for Childhood Obesity: A Multisite Randomized Clinical Trial - Wilfley, Denise E; Saelens, Brian E; Stein, Richard I; Best, John R; Kolko, Rachel P; Schechtman, Kenneth B; Wallendorf, Michael; Welch, R Robinson; Perri, Michael G; Epstein, Leonard H (JAMA pediatrics, 2017)
Elucidation of optimal dosing and treatment content is critical for health care providers, payers, and policy makers, as well as mechanisms of change to inform intervention delivery and training initiatives for childhood obesity. To evaluate effects, following a 4-month family-based behavioral weight loss treatment (FBT), of 2 doses (HIGH or LOW) of a weight-control intervention (enhanced social facilitation maintenance [SFM+]) vs a weight-control education condition (CONTROL; matched for dose with LOW), on child anthropometrics, and to explore putative mediators of weight loss outcomes. For this parallel-group randomized clinical trial conducted at 2 US academic medical centers from December 2009 to March 2013, 172 parent-child dyads completed FBT and were then randomized to 8 months of SFM+ (HIGH, n = 59; LOW, n = 56) or CONTROL (n = 57). Children (aged 7-11 years) with overweight and obesity (body mass index [BMI; calculated as weight in kilograms divided by height in meters squared] ≥85th percentile) with at least 1 parent with overweight and obesity (BMI ≥25) were recruited. HIGH SFM+ vs LOW SFM+ (CONTROL matched the dose of LOW). Intention-to-treat analysis using mixed-effects models estimated change in child percentage overweight (percentage above the median BMI for a child's age and sex) for the FBT period (0-4 months) and the SFM+ period (4-12 months), and proportion of children achieving a clinically significant change in percentage overweight (≥9-unit decrease; months 0-12). Theory-based outcome mediators were also evaluated. This study recruited 172 parent-child dyads (mean [SD] age: parents 42.3 [6.4] years; children, 9.4 [1.3] years). The omnibus treatment × time interaction for child percentage overweight was significant (F8, 618.9 = 2.89; P = .004). Planned pairwise comparisons revealed that from months 4 to 12, LOW had better outcomes than CONTROL (difference, -3.34; 95% CI, -6.21 to -0.47; d = -0.40; P = .02). HIGH had better outcomes than LOW (difference, -3.37; 95% CI, -6.15 to -0.59; d = -0.38; P = .02) and CONTROL (difference, -6.71; 95% CI, -9.57 to -3.84; d = -0.77; P < .001). A greater proportion of children in HIGH (45 [82%]) vs LOW (34 [64%]) (difference, 18.00; 95% CI, 1.00-34.00; P = .03; number needed to treat = 5.56) and CONTROL (25 [48%]) (difference, 34.00; 95% CI, 16.00-51.00; P < .001; number needed to treat = 2.94) had clinically significant percentage overweight reductions. Food and activity monitoring and goal setting mediated the effect of LOW vs CONTROL (50%). Monitoring and goal setting, family and home environment, and healthy behaviors with peers mediated the effect of HIGH vs CONTROL (25%-42%). Following FBT, specialized intervention content (SFM+) enhanced children's weight outcomes and outperformed a credible control condition, with high dose delivery yielding the best outcomes. Sustained monitoring and goal setting, support from the family and home environment, and healthy peer interactions explained outcome differences, highlighting key treatment targets. clinicaltrials.gov Identifier: NCT00759746.